Lamellar Nanoporous Metal/Intermetallic Compound Heterostructure Regulating Dendrite‐Free Zinc Electrodeposition for Wide‐Temperature Aqueous Zinc‐Ion Battery - Meng, Huan; Ran, Qing; Dai, Tian‐Yi; Jia, Jian‐Hui; Liu, Jie; Shi, Hang; Han, Gao‐Feng; Wang, Tong‐Hui; Wen, Zi; Lang, Xing‐You; Jiang, Qing (Advanced materials (Weinheim), 2024)
Aqueous zinc‐ion batteries are attractive post‐lithium battery technologies for grid‐scale energy storage because of their inherent safety, low cost and high theoretical capacity. However, their practical implementation in wide‐temperature surroundings persistently confronts irregular zinc electrodeposits and parasitic side reactions on metal anode, which leads to poor rechargeability, low Coulombic efficiency and short lifespan. Here, this work reports lamellar nanoporous Cu/Al2Cu heterostructure electrode as a promising anode host material to regulate high‐efficiency and dendrite‐free zinc electrodeposition and stripping for wide‐temperatures aqueous zinc‐ion batteries. In this unique electrode, the interconnective Cu/Al2Cu heterostructure ligaments not only facilitate fast electron transfer but work as highly zincophilic sites for zinc nucleation and deposition by virtue of local galvanic couples while the interpenetrative lamellar channels serving as mass transport pathways. As a result, it exhibits exceptional zinc plating/stripping behaviors in aqueous hybrid electrolyte of diethylene glycol dimethyl ether and zinc trifluoromethanesulfonate at wide temperatures ranging from 25 to −30 °C, with ultralow voltage polarizations at various current densities and ultralong lifespan of >4000 h. The outstanding electrochemical properties enlist full cell of zinc‐ion batteries constructed with nanoporous Cu/Al2Cu and ZnxV2O5/C to maintain high capacity and excellent stability for >5000 cycles at 25 and −30 °C. Lamellar nanoporous Cu/Al2Cu heterostructure electrodes with high electron/ion transportability and abundant zincophilic sites are constructed as high‐performance anode host materials for wide‐temperature aqueous zinc ion batteries. Benefiting from the unique metal/intermetallic compound heterostructure to form local galvanic couples to facilitate Zn nucleation and deposition, nanoporous Cu/Al2Cu electrode exhibits ultralong‐lifespan stability at 25 and −30 °C.